The History of Kedatukan Sunggal Serbanyaman, 1896-1946 - Agam Husein Wibowo; Irwansyah Irwansyah; Muhammad Faishal (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
This research aims to uncover the historical significance of Kedatukan Sunggal Serbanyaman, its role within the Sultanate, its historical heritage, and preservation efforts. Employing a qualitative descriptive historical research method, data were collected through field studies, observations, and interviews with key figures including the Raja Kepala Adat Kedatukan Sunggal Serbanyaman descendants, Malay culturalists, and relevant literature. Findings reveal that Kedatukan Sunggal Serbanyaman, founded by Adir in 1629 with pepper as its main commodity, is a significant Malay kingdom in North Sumatra and part of Medan's four tribes. The research highlights the kingdom's power, evidenced by the Sunggal War against the Dutch (1872-1895), and notes the decline in its nobility's prominence following the East Sumatra Social Revolution of 1946, which led to the loss of most of its heritage except for the Grand Mosque and the grave complex of Datuk Sulung Barat and descendants.